Machiavelli and the Politics of Democratic Innovation - Holman, Christopher (Book collections on Project MUSE., 2018)
This book critically reevaluates the political thought of Niccolò Machiavelli, demonstrating the extent to which he can be seen to formulate a unique ethical foundation for democratic practice that is grounded in the creative orientation of all individuals.